Analisis Kebutuhan Pengembangan Lembar Kerja Murid Elektronik (E-LKM) Berbasis Problem Based Learning Terintegrasi Sustainable Development Goal (SDG) 15 pada Materi Ekosistem Fase E - Regina Faradika; Zulyusri Zulyusri (Al-Alam: Islamic Science Education Journal, 2026)
This study aims to analyze the need for developing learning media. Research subjects were selected using purposive sampling, comprising two biology teachers and 33 students from class X E 6. The study employed descriptive qualitative and quantitative methods within an R&D framework using the 4D model, limited to the "develop" stage. Data collection involved teacher interviews and the distribution of student needs questionnaires. Research instruments included a teacher interview guide and a student needs questionnaire. The analysis revealed that teachers faced limitations regarding time and technological proficiency in developing diverse learning media and had not yet integrated sustainability issues; students also encountered obstacles when using existing learning media. Student analysis showed that 54.54% preferred worksheets, 24.24% desired media featuring videos or animations, and 90.90% (72.72% agreeing and 18.18% strongly agreeing) supported learning linked to environmental issues. Task analysis was based on the Phase E biology Learning Outcomes, with assignments formulated according to the Problem-Based Learning (PBL) syntax. Concept analysis covered ecosystem components, energy flow, and biogeochemical cycles, integrating SDG 15 indicators. The task and concept analyses served as the basis for formulating learning objectives. Consequently, it is concluded that the development of an SDG 15-integrated, PBL-based electronic student worksheet for the Phase E ecosystem topic is necessary to meet the need for interactive, contextual learning media that introduces sustainability issues.